2018
DOI: 10.1111/cas.13506
|View full text |Cite
|
Sign up to set email alerts
|

Present status and future perspective of peptide‐based vaccine therapy for urological cancer

Abstract: Use of peptide‐based vaccines as therapeutics aims to elicit immune responses through antigenic epitopes derived from tumor antigens. Peptide‐based vaccines are easily synthesized and lack significant side‐effects when given in vivo. Peptide‐based vaccine therapy against several cancers including urological cancers has made progress for several decades, but there is no worldwide approved peptide vaccine. Peptide vaccines were also shown to induce a high frequency of immune response in patients accompanied by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 67 publications
(127 reference statements)
1
39
0
Order By: Relevance
“…Cancer vaccine therapy is one of the major immunotherapies, which induces specific anti‐cancer activity of lymphocytes through administration of specific cancer antigens . There are several methodologies, one of which is administering the identified cancer antigen peptide or protein with an adjuvant, and the other is transferring autologous lymphocytes that acquire tumor specificity by antigen stimulation . In addition, another strategy is the use of an autologous cancer vaccine cell, which has been made more immunogenic by transferring a cytokine or chemokine gene .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer vaccine therapy is one of the major immunotherapies, which induces specific anti‐cancer activity of lymphocytes through administration of specific cancer antigens . There are several methodologies, one of which is administering the identified cancer antigen peptide or protein with an adjuvant, and the other is transferring autologous lymphocytes that acquire tumor specificity by antigen stimulation . In addition, another strategy is the use of an autologous cancer vaccine cell, which has been made more immunogenic by transferring a cytokine or chemokine gene .…”
Section: Discussionmentioning
confidence: 99%
“…3 There are several methodologies, one of which is administering the identified cancer antigen peptide or protein with an adjuvant, and the other is transferring autologous lymphocytes that acquire tumor specificity by antigen stimulation. 4,5 In addition, another strategy is the use of an autologous cancer vaccine cell, which has been made more immunogenic by transferring a cytokine or chemokine gene. 6 This treatment has had an excellent therapeutic effect for urological cancers, especially prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…65 Peptide-based vaccination is a key role of combining a specific, desirable immune response, easy production, less laboring, with minimal immunological hazards, combining both T-cell and Bcell epitopes and could be used for both prevention or as a therapeutic tool . 66,67 peptide vaccine is poorly immunogenic when used alone, thus, a substance that facilitates and enhance antigenantibody binding (adjuvant) is needed for better immune response. 68 Future studies are required and highly recommended to subject these suggested peptides for clinical trials and select a suitable delivery system or adjuvant and strategies which could improve in-vivo and in-vitro Tcell and B-cell immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Obara et al [31] reports that in urological cancer cases the immune response of small peptides has been rather limited due to various factors Perhaps the most individualistic drug ever made is the case of manufacture of milasen, a splice-modulating antisense oligonucleotide drug tailored to one particular patient to treat a fatal but rare neurodegenerative condition [32]. The exercise was facilitated by molecular diagnosis that led to the rational design, testing and manufacture of the novel drug and offers a possible template for future development of patient-customized therapeutics.…”
Section: Personalized Vaccinesmentioning
confidence: 99%